Exploring theoretical mechanisms of community-engaged research: a multilevel cross-sectional national study of structural and relational practices in community-academic partnerships - John G. Oetzel; Blake Boursaw; Maya Magarati; Elizabeth Dickson; Shannon Sanchez-Youngman; Leo Morales; Sarah Kastelic; Milton "Mickey" Eder; Nina Wallerstein (BMC, 2022)
Abstract Background Community-Based Participatory Research (CBPR) is often used to address health inequities due to structural racism. However, much of the existing literature emphasizes relationships and synergy rather than structural components of CBPR. This study introduces and tests new theoretical mechanisms of the CBPR Conceptual Model to address this limitation. Methods Three-stage online cross-sectional survey administered from 2016 to 2018 with 165 community-engaged research projects identified through federal databases or training grants. Participants (N = 453) were principal investigators and project team members (both academic and community partners) who provided project-level details and perceived contexts, processes, and outcomes. Data were analyzed through structural equation modeling and fuzzy-set qualitative comparison analysis. Results Commitment to Collective Empowerment was a key mediating variable between context and intervention activities. Synergy and Community Engagement in Research Actions were mediating variables between context/partnership process and outcomes. Collective Empowerment was most strongly aligned with Synergy, while higher levels of Structural Governance and lower levels of Relationships were most consistent with higher Community Engagement in Research Actions. Conclusions The CBPR Conceptual Model identifies key theoretical mechanisms for explaining health equity and health outcomes in community-academic partnerships. The scholarly literature's preoccupation with synergy and relationships overlooks two promising practices-Structural Governance and Collective Empowerment-that interact from contexts through mechanisms to influence outcomes. These results also expand expectations beyond a "one size fits all" for reliably producing positive outcomes.